2014
DOI: 10.7874/kja.2014.18.3.126
|View full text |Cite
|
Sign up to set email alerts
|

Benign Paroxysmal Positional Vertigo with Simultaneous Involvement of Multiple Semicircular Canals

Abstract: Background and ObjectivesBenign paroxysmal positional vertigo (BPPV) generally involves a single semicircular canal (single canal BPPV) but it has been reported that more than one semicircular canal on either the same or the opposite side can be involved in 6.8-20% of the cases (multiple canal BPPV). In this study, the clinical characteristics of multiple canal BPPV were analyzed and compared to those of single canal BPPV.Materials and MethodsRetrospective analysis was performed on 1054 consecutive patients di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
39
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 15 publications
8
39
1
Order By: Relevance
“…On the contrary, our population was characterised by considerably more horizontal BPPV and multi-canal BPPV than previous estimates that range from around 6-10 % [14,16,28,30] and less than 8 % [13,16,31], respectively. Many studies do not investigate cupulolithiasis that accounted for 39 % of our patients.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…On the contrary, our population was characterised by considerably more horizontal BPPV and multi-canal BPPV than previous estimates that range from around 6-10 % [14,16,28,30] and less than 8 % [13,16,31], respectively. Many studies do not investigate cupulolithiasis that accounted for 39 % of our patients.…”
Section: Discussioncontrasting
confidence: 76%
“…We argue that some of these likely have recovered from BPPV, reducing motivation for further contact to the clinic. Regardless of treatment or spontaneous remission, there is often a relapse in BPPV mostly within the first year and the relapse rate after 5 years is 33-50 % with higher incidence among BPPV secondary to trauma [23,29,31,32]. In our population, 12 % of the patients experienced relapse approximately year after ended treatment.…”
Section: Discussionmentioning
confidence: 78%
“…In mixed-type vertigo, most prevalent combinations seen are posterior and horizontal canal pathologies, as was the case with our patient [1, 2, 4]. In a multicenter study presented by Leopardi et al, in only 4.4% of BPPV cases were multi-canal etiologies observed, and the authors reported combination of posterior and horizontal canal pathologies as most frequently seen type of BPPV [9].…”
Section: Discussionsupporting
confidence: 77%
“…An incidence of up to 10% of bilateral posterior canal BPPV among BPPV cases has been reported in several studies [2][3][4][5][6][7][8]. Thus if the Dix-Hallpike test should not be repeated with the opposite side when the test on initial side is positive, potential cases with bilateral posterior canal BPPV would not be diagnosed and treated appropriately.…”
mentioning
confidence: 99%
“…Multicanal BPPV may also simultaneously involve in the posterior and lateral canals, either on the same side or on 2 sides, with a reported incidence of up to 13% among BPPV cases [4][5][6][7][8]. Thus if the supine roll test to evaluate lateral canal BPPV should not be performed since the patient presents with a history corresponding BPPV and shows a positive DixHallpike test, potential cases with multicanal BPPV involving the posterior and lateral canals would not be diagnosed and treated appropriately.…”
mentioning
confidence: 99%